An Index of African Monetary Integration (IAMI) - Samba Diop; Simplice Asongu (African Governance and Development Institute (AGDI), 2020)
This study improves the African Regional Integration Index (ARII) proposed by the African Union, the African Development Bank and the United Nations Economic Commission for Africa by providing a theoretical framework and addressing shortcomings related to weighting and aggregation of the indicator. This paper measures monetary integration in the eight African Regional Economic Communities (RECs) by constructing an Index of African Monetary Integration (IAMI). It proposes an Optimal Currency Area as theoretical framework and uses a panel approach to appreciate the dynamics of the index over different periods of time. The findings show that: (i) inflation and finance (trade and mobility) present the highest (lowest) score while ECOWAS is (EAC and IGAD are) the highest (least) performing. (ii) Surprisingly, in most RECs, the highest contributors to wealth creation are not the top performers in regional monetary integration. (iii) The RECs in Africa are characterized by a stable monetary integration which is different from the gradual process usually observed in monetary integration because with the exception of the EAC and UMA, the dynamics of IAMI show a steady trend in the overall index across time. Policy implications are discussed.
Keywords: E10; E50; O10; O55; P50; 330; Monetary Integration; Currency Unions; Economic Communities; Africa